An Autologous Topical Serum Derived from Platelet-Rich Plasma Therapy for the Management of Sensitive Skin Alterations: A Case Series Report - García-Millan C; Pino A; Rodrigues R; Segurado-Miravalles G; Alegre-Sánchez A; Jaén P; Anitua E (Dove Medical Press, 2022)
Cristina García-Millan,1 Ander Pino,2 Rita Rodrigues,1 Gonzalo Segurado-Miravalles,1,3 Adrián Alegre-Sánchez,1 Pedro Jaén,1,3 Eduardo Anitua2 1Grupo de Dermatología Pedro Jaén, Madrid, Spain; 2BTI Biotechnology Institute, Vitoria, Spain; 3University Hospital Ramon y Cajal, Madrid, SpainCorrespondence: Eduardo Anitua, BTI Biotechnology Institute, Jacinto Quincoces 39, Vitoria, Spain, Email eduardo@fundacioneduardoanitua.orgBackground: Although the underlying pathophysiology of sensitive skin remains unknown, it presents clinical symptoms like erythema, burning and dryness associated with other inflammatory dermatoses such as dermatitis or rosacea.Objective: The aim of the present report was to provide preliminary data about the efficacy of Endoret-Serum (ES) as an autologous therapy for the topical management of sensitive skin alterations.Materials and Methods: Five patients underwent a daily topical ES treatment that was maintained for three months. Clinical assessment was carried out using validated dermatological surveys (DLQI, IGA, Likert, PGI-I). Additionally, skin hydration measurement and high-resolution topographic and reflectance confocal imaging analysis were carried out.Results: No adverse events were observed during the treatment. At the end of the follow-up period, surveys highlighted a significant therapeutic effect compared to baseline. Skin hydration was also improved, and topographic images showed a decrease in patient's underlying inflammatory and vascular condition.Conclusion: This preliminary report suggests that Endoret-Serum may be useful in the management of clinical symptoms derived from sensitive skin alterations.Keywords: platelet-rich plasma, growth factors, sensitive skin, topical formulation, case report